Salt precipitation of a crude extract with cellulolytic activity produced by Aspergillus niger UC33 - Morales Borrell, Dayana; Baryolo González, Linnet; Mora González, Néstor; Ramos Sánchez, Luis Beltrán; Pérez Sánchez, Amaury (Revista Colombiana de Investigaciones Agroindustriales, 2022)
The purification of cellulase enzymes is a critical step for their production because it is often very expensive. The objective of this study was to evaluate the saline precipitation of cellulases produced by Aspergillus niger UC33 in solid-state fermentation, to increase the yield and purity of the enzyme at the lowest possible cost. The Design-Expert 11.1.2 program was used for the experimental design and the optimization of the experimental conditions. Ammonium sulfate between 60 and 90 % saturation was used for precipitation, among 1 and 3 h of precipitation time were employed and the temperatures applied were 4 and 25 °C. The optimal conditions found to maximize yield and purity were 68.97% saturation with ammonium sulfate, precipitation time of 1.28 h and temperature of 25 °C. Under these conditions, the yield, purity and cost values ​​were: 74.81%, 1.26 and USD 0.2609, respectively. The molecular weight of the enzyme was 38.47 kDa and the cellulolytic activity was 31.854 IU.